Distinct effects of obesity and puberty on risk and age at onset of pediatric MS. Issue 12 (4th November 2016) - Chitnis, Tanuja; Graves, Jennifer; Weinstock‐Guttman, Bianca; Belman, Anita; Olsen, Cody; Misra, Madhusmita; Aaen, Gregory; Benson, Leslie; Candee, Meghan; Gorman, Mark; Greenberg, Benjamin; Krupp, Lauren; et al.
Abstract: Objective: The aim of this study was to examine the relative contributions of body mass index (BMI) and pubertal measures for risk and age of onset of pediatric MS. Methods: Case–control study of 254 (63% female) MS cases (onset<18 years of age) and 420 (49% female) controls conducted at 14 U.S. Pediatric MS Centers. Sex‐ and age‐stratified BMI percentiles were calculated using CDC growth charts from height and weight measured at enrollment for controls, and within 1 year of onset for MS cases. Sex‐stratified associations between MS risk and age at symptom onset with both BMI and pubertal factors were estimated controlling for race and ethnicity. Results: Only 11% of girls and 15% of boys were prepubertal (Tanner stage I) at MS onset. 80% of girls had onset of MS after menarche. BMI percentiles were higher in MS cases versus controls (girls: P < 0.001; boys: P = 0.018). BMI was associated with odds of MS in multivariate models in postpubertal girls (OR = 1.60, 95% confidence interval [CI]: 1.12, 2.27, P = 0.009) and boys (OR = 1.43, 95% CI: 1.08, 1.88, P = 0.011). In girls with MS onset after menarche, higher BMI was associated with younger age at first symptoms ( P = 0.031). Younger menarche was associated with stronger effects of BMI through mediation and interaction analysis. In pubertal/postpubertal boys, 89% of whom were obese/overweight, earlier sexual maturity was associated with earlier onset of MS ( P < 0.001). Interpretation: Higher BMI in early adolescence is a risk factor for MS in girls and boys. Earlier age at sexual maturity contributes to earlier age at MS onset, particularly in association with obesity.